2020
DOI: 10.1182/blood-2020-138794
|View full text |Cite
|
Sign up to set email alerts
|

Children and Young Adults Admitted to a NYC Children's Hospital Had a Similar Rate of Severe COVID-19 Coagulopathy As That Reported in Older Adults

Abstract: The coagulopathy associated with COVID-19 has not been previously described in children and young adults. We reviewed the clinical and laboratory characteristics of children and young adults admitted for COVID-19 to an urban Children's Hospital in New York City, focusing on coagulation and venous thromboembolism. Clinical and laboratory data were analyzed from 54 patients aged 2 months to 30 years treated by the Pediatric Hematology service at a single Children's Hospital between January 1 and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Considering the pathophysiological aspects of sickle cell disease and the clinical observations made during the H1N1 epidemic, most experts prepared for a potential catastrophe regarding this group when the COVID-19 pandemic first became established. However, a fair number of case reports and case series have revealed surprisingly positive clinical courses and outcomes in this population (35,36,46,50,56,60,62,75,81,84,91).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Considering the pathophysiological aspects of sickle cell disease and the clinical observations made during the H1N1 epidemic, most experts prepared for a potential catastrophe regarding this group when the COVID-19 pandemic first became established. However, a fair number of case reports and case series have revealed surprisingly positive clinical courses and outcomes in this population (35,36,46,50,56,60,62,75,81,84,91).…”
Section: Discussionmentioning
confidence: 96%
“…Some studies suggest an elevated incidence of pulmonary embolism in people with sickle cell disease and COVID- 19 (16, 43, 53, 72, 79, 103). However, case series, such as those conducted by Mitchell et al (60) and Noisette et al (62), present divergent data in this regard. Even more recently, in their cohort of 281 patients with sickle cell disease and COVID-19, Singh et al (108) found no significant differences in rates of venous thromboembolism compared to the group of patients with sickle cell disease hospitalized for other reasons than SARS-CoV-2 infection.…”
Section: Therapeutic Optionsmentioning
confidence: 96%